The clinical case of treatment of combined endo-perio lesion (Эндодонтия Today, 2020)
This paper presents a complex clinical case of retreatment of teeth 3.5 and 3.6 with combined endodonticperiodontal lesion. The inflammatory process in periodontium was initiated by errors in primary endodontic treatment - root was perforated when installing metal posts, and because of a close anatomical and topographic relationship between the dental pulp and periodontal tissues. Necrosis of the pulp leads to the development of the infection in periodontal tissue and the periodontal disease. Poor quality primary endodontic treatment of 3.5 and 3.6 led to the development of apical periodontitis and the inflammatory process in the periodontium. The successful result of recurrent endodontic treatment is presented.